THE THEME OF THE DECLINE OF A NOBLE FAMILY IN M. E. SALTYKOV-SHCHEDRIN’S NOVEL “THE GOLOVLYOV FAMILY” - Yuldasheva , Diana; Ischanova , Dilbar (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The Golovlyov Family reflects the era contemporary to the great Russian satirical writer, in which, as M. E. Saltykov-Shchedrin perceived, family ties lose their meaning and significance, human relationships collapse, and are increasingly replaced by spiritual emptiness, hypocrisy, verbosity, deceit, and baseness. The family chronicle of a decaying noble lineage leads the characters to an inevitable tragic finale, from which even a belated realization cannot save them.